Breastfeeding Duration and Childhood Caries: A Cohort Study - Areerat Nirunsittirat (2018)
© 2016 S. Karger AG, Basel. This cohort study was conducted in Khon Kaen, Thailand, to test the hypothesis that a longer breastfeeding duration increases the risk for dental caries in primary teeth. We collected information on infant feeding practices and potential confounders using a structured questionnaire to interview mothers or caregivers during the second trimester of pregnancy and after birth at 21 days and at 3, 12, 18, 24, and 36 months. Regardless of other liquids and foods, full breastfeeding was defined as feeding breast milk but not formula, while any breastfeeding was feeding breast milk with or without formula. Two calibrated dentists measured dental caries when the children were 3-4 years of age using the decayed, missing, and filled surfaces (dmfs) index following the World Health Organization criteria. Negative binomial regression with a generalized linear model was used to estimate relative risks (RRs) and 95% confidence intervals (CIs) using dmfs as an outcome. Log-binomial regression was performed to model the caries prevalence. Of 556 children, 88.1% had dental caries with a mean dmfs of 14.2. Full breastfeeding for 6-11 months was significantly associated with a lower dmfs (adjusted RR 0.77, 95% CI 0.63, 0.93) and a lower caries prevalence (adjusted RR 0.45, 95% CI 0.22, 0.90). The frequency of sleeping while breast- or bottle-feeding increased the caries risk in a dose-response manner. There was no association between duration of any breastfeeding and dental caries. In conclusion, full breastfeeding for 6-11 months may protect against dental caries in primary teeth. Prolonged breastfeeding was not associated with dental caries in this population.